Implementasi Teknologi Komunikasi Data Menggunakan Open System Interconnection (OSI) Untuk Berkirim Pesan Antar Perangkat - Susilawati Susilawati; Marcel Ade Satria; Khaila Mardina; Juniwan Juniwan; Didik Aribowo (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Currently, the development of communication networks has influenced how humans communicate and exchange information. Data communications technology reflects the rapid evolution in the way humans communicate and exchange information. Data communication is the process of exchanging information between two or more devices via a transmission medium, such as cables, radio waves, or other network infrastructure. The goal of data communications is to transfer data from one location to another quickly, efficiently, and accurately. The method used is to look for references from several internet sources such as Google. The OSI model has 7 layers, namely Application Layer, Presentation layer, Session Layer, Transport layer, Network layer, data link layer, physical layer